Effect of Ceramic Dust as Partial Replacement of Cement on Lightweight Foamed Concrete - Lee, Yee Ling; Lim, Siong Kang; Lim, Ming Han; Lee, Foo Wei; Yew, Ming Kun (International Journal of Integrated Engineering, 2021)
Disposal of waste into the landfill causes a severe impact on the environment. One of the waste products is ceramic waste. Ceramic waste has some excellent properties in its durability, hardness, and highly resistant to biological, chemical, and physical degradation forces. These excellent properties of the ceramic waste may make it suitable to be used in concrete. This study investigates the effect on the compressive strength of lightweight foamed concrete with different percentage of ceramic dust replacement level towards the cement and three different levels of water-cement ratio. 0%, 5%, 15%, and 25% of replacement level with 0.52, 0.56, and 0.60 water-cement ratios respectively for each replacement level was used as the parameter to investigate the fresh properties, and strength performance of lightweight foamed concrete. The stability and consistency of every mix are studied as well. From this study, it was observed that the incorporation of ceramic waste dust partially replaced the cement did not affect on the fresh properties of the foamed concrete. However, the compressive strength of foamed concrete affected by ceramic waste dust partially replaced the cement.